(untitled) (Research, Society and Development, 2021)
Introduction: Ameloblastoma is a benign neoplasm characterized by the proliferation of odontogenic epithelium that mainly affects the gnathic bones and, due to its invasive and expansive growth, presents high rates of recurrence to surgical treatment. Among the most conservative treatments are enucleation and marsupialization; among radicals, resections are more widespread. Objective: The objective is to present, through a case report, conservative surgical treatment with enucleation followed by the use of the Carnoy solution. Case report: A 24-year-old male patient arrives at the outpatient clinic of Hospital da Restauração with painful complaints of mild and constant intensity in the region of the left mandibular angle, with an evolution of three weeks. After a panoramic X-ray, the presence of the included 38 tooth was associated with an extensive unilocular radiolucent lesion, surrounding the angle and mandibular ramus. Preoperative examinations were performed for incisional biopsy. Histopathological diagnosis was unicystic ameloblastoma. In view of the histopathology obtained, we opted for enucleation of the lesion with concomitant use of direct Carnoy solution in the region of the lesion. Discussion: The choice of therapeutic behavior depends on the size, type of lesion, location and histopathology. After the surgical decision, a radiographic clinical follow-up is necessary to assess possible recurrences. Carnoy’s solution is a cauterizing agent with moderate tissue penetration, rapid local fixation and hemostatic action, whose surgical use in cystic lesions has occurred since the beginning of the 20th century. Conclusion: Conservative treatment with the enucleation technique followed by complementary therapy using Carnoy’s solution proved to be quite effective.